2013
DOI: 10.1353/hpu.2013.0139
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Colorectal Cancer Screening Uptake Among Average-Risk Insured American Indian/Alaska Native and White Women

Abstract: Introduction American Indian and Alaska Native (AI/AN) women have among the lowest rates of colorectal cancer (CRC) screening. Whether screening disparities persist with equal access to health care is unknown. Methods Using administrative data from 1996-2007, we compared CRC screening events for 286 AI/AN and 14,042 White women aged 50 years and older from a health maintenance organization in the Pacific Northwest of the U.S. Results The proportion of AI/AN and White women screened for CRC at age 50 was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…This was unexpected finding and deserves further investigation in future studies. However, variations in CRC screening uptake among Native Americans and Asian subgroups have been documented 50,51 ; therefore, an examination of pathways to CRC screening or other health services utilization in those populations is warranted. 12,14,21,23 There are limitations to this study that must be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was unexpected finding and deserves further investigation in future studies. However, variations in CRC screening uptake among Native Americans and Asian subgroups have been documented 50,51 ; therefore, an examination of pathways to CRC screening or other health services utilization in those populations is warranted. 12,14,21,23 There are limitations to this study that must be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we did not attempt to assess differences in the pathways to CRC screening among other racial/ethnicity groups, because it was beyond the scope of this study. However, variations in CRC screening uptake among Native Americans and Asian subgroups have been documented 50,51 ; therefore, an examination of pathways to CRC screening or other health services utilization in those populations is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In general, insurance is a major contributor to disparities in preventive care, but education, income, cultural attitudes, language, and a usual source of care are also factors (91,95,111). Differences in patient reports in provider recommendations by race or ethnicity are relatively infrequent and small.…”
Section: Preventive Carementioning
confidence: 99%
“…For Native populations burdened by extreme health disparities, ethnic identity has been explored relative to general health and the related influence on preventive behaviors and behavioral compliance with medical recommendations [ 9 , 12 , 13 , 14 ]. Some studies have shown that a strong sense of ethnic identification is associated with higher rates of optimal health beliefs and behaviors [ 15 , 16 , 17 , 18 , 19 , 20 ] and better health outcomes [ 9 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, an inverse relationship between ethnic identity and health-promoting behaviors has been discerned. In particular, strong ethnic identity has been linked to suboptimal health behaviors related to tobacco and drug use [ 9 , 14 ] and reduced adherence with cancer screening recommendations [ 12 , 13 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%